2008
DOI: 10.1016/j.jtcvs.2008.05.054
|View full text |Cite
|
Sign up to set email alerts
|

The sinus of Valsalva relieves abnormal stress on aortic valve leaflets by facilitating smooth closure

Abstract: Sinuses of Valsalva facilitate the smooth closure of the aortic valve, thereby avoiding the building up of abnormal stress in the leaflet. Such an effect may assure the durability of valve leaflets in aortic grafts with a pseudosinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 27 publications
1
75
1
Order By: Relevance
“…As the unstressed valve state popular choice is a nearly closed [18,25,27,38,39,40,41] or fully-open configuration [16,17,20]. Fully-closed position selection (loaded tissues behavior) [27,42,43,44] requires to assume the size and shape of the contact area in the coaptation regions of the leaflets. Experimental validation of aortic valve prosthesis initial geometry is important for independent validation of the results of the analysis with either experimental data or prior published results in the application of such analyses for complex biological flow phenomena.…”
Section: Fig 1 Aortic Valve Leaflet Regions [27]mentioning
confidence: 99%
See 1 more Smart Citation
“…As the unstressed valve state popular choice is a nearly closed [18,25,27,38,39,40,41] or fully-open configuration [16,17,20]. Fully-closed position selection (loaded tissues behavior) [27,42,43,44] requires to assume the size and shape of the contact area in the coaptation regions of the leaflets. Experimental validation of aortic valve prosthesis initial geometry is important for independent validation of the results of the analysis with either experimental data or prior published results in the application of such analyses for complex biological flow phenomena.…”
Section: Fig 1 Aortic Valve Leaflet Regions [27]mentioning
confidence: 99%
“…De Hart et al [23] draws attention to the fact that fiberreinforcement has an impact on transvalvular pressure gradient. In many previous works the anisotropic nature of the leaflet tissue is represented by means orthotropic [25,27,42,48], transverse anisotropic [5,6,49] or hyperelasticity, what according to other researchers [27,50] is not capable of capturing the real deformation-dependent anisotropy of aortic valve tissue. Burriesci et al [51] concluded that even a relatively low presence of orthotropy will significantly alter the stress distributions of the valve.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…In most cases, the dimensions of the three leaflets are slightly unequal (Roberts, 1970). The dynamic, complex three-dimensional anatomy of the aortic trileaflet cusps and the aortic root allows for stress sharing between leaflets, the sinuses of Valsalva, and the aortic wall (Thubrikar et al, 1986a, Katayama et al, 2008.…”
Section: Aortic Valve Anatomymentioning
confidence: 99%
“…Therefore, There are three aortic sinuses corresponding to the respective leaflets. These sinuses play an important role in minimising leaflet stress and strain [4] by helping to evenly distribute the diastolic pressure load across the leaflets and the sinus wall through the formation of a relatively spherical shape together with the valve cusps. A spherical surface is the shape that gives the minimal surface area for a given volume, thus minimising the stress forces on the leaflets in diastole.…”
Section: Valve In Open Positionmentioning
confidence: 99%